(3JWHjbGJ bhGYO GdHjGfGJ HGSJNOGe (Bjavas - (3geGe TeSi (B.s; (3LeGd HWjN , eQGLY(B.s ((3MdH (B:s (3TYGY ddfTQ h GdYdhe(B,s, 2004)
(3HfGA JWHjbGJ bhGYO GdHjGfGJ HGSJNOGe dZI (Bjava.s
(3jJfGhd GdcJGH JWHjbGJ bhGYO GdHjGfGJ(B.s
All age.
Keywords: (3dZGJ HQeLg(B.s